Reconstitution of Acetylcholinesterase into Liposomes and Electrochemical Assay of Its Activity and Inhibition by Methyl Parathion - Wang, Yuhui; Chen, Jin; Ren, Qiaoqiao; Miao, Jigen (Asian Journal of Chemistry, 2011)
A biomimetic structure was constructed by reconstituting acetylcholinesterase (AChE) into liposomes for the electrochemical determination of methyl parathion using square wave voltammetry. Compared with free AChE, the michaelis constant (Km) drops and the maximum reaction rate (Vmax) increases for the reconstituted AChE. Several parameters for the experiments were optimized including the concentration of liposome and acetone, the time of enzyme reaction and the time of AChE inhibition by methyl parathion. The logarithmic plot of inhibition rate versus methyl parathion shows a close linearity ranging from 0.1 ng/mL to 1 μg/mL. The detection limit is calculated to be 0.49 ng/mL at 10 % inhibition. The reconstituted AChE exhibits improved performance of enzymatic activity and inhibition sensitivity since the biomimetic structure offers a microenvironment close to the situation of natural enzyme in vivo. Bio-inspired AChE-liposome system shows the potential to provide a promising and sensitive medium in organophosphates assay with AChE.